Toward a taxonomy of micro and small manufacturing enterprises - Wibowo, Budhi; Masrurah, Nur Aini; Kasanah, Yulinda Uswatun; Trapsilawati, Fitri; Subagyo; Ilhami, Muhammad Adha (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2019)
The business sustainability of micro and small manufacturing enterprises (M-MSEs) are substantial to drive productivity and employment rate in many developing countries. However, due to various limitations, these enterprises are struggling to develop themselves into larger enterprises. For this reason, the government of Indonesia is enthused to provide technical and managerial supports for these M-MSEs. This study aims to provide an objective taxonomy of Indonesian M-MSEs as a guidance for the authorities to deliver the appropriate supports. The taxonomy was developed based on the survey to 735 M-MSEs in the Yogyakarta area. By using cluster analysis, we found that the M-MSEs can be classified into four distinct groups. Each group has its development strategies, ranging from adopting lean philosophy to instituting relationship marketing. This taxonomy provides useful directions for the authorities to support the development of M-MSEs in Yogyakarta and also serves as part of a broader effort to construct M-MSEs taxonomy in Indonesia.